2011
DOI: 10.1007/s10157-011-0568-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of glomerular renin−angiotensin system (RAS) activation in the development and progression of glomerular injury

Abstract: Recently, there has been a paradigm shift away from an emphasis on the role of the endocrine (circulating) renin−angiotensin system (RAS) in the regulation of the sodium and extracellular fluid balance, blood pressure, and the pathophysiology of hypertensive organ damage toward a focus on the role of tissue RAS found in many organs, including kidney. A tissue RAS implies that RAS components necessary for the production of angiotensin II (Ang II) reside within the tissue and its production is regulated within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
1
23
0
5
Order By: Relevance
“…Although the precise mechanism of action of RAS is currently unknown, we hypothesize that increased renal renin production caused by severe inflammation has an important role in scar formation because the renin content is reportedly increased depending on the severity of interstitial fibrosis in scarred kidneys. 26,27 As AGT is the only renin substrate in the renal RAS, 18 increased renin produces Ang I from AGT. Ang II converted from increased Ang I induces the expression of transforming growth factor-b1 and causes renal fibrosis through multiple mechanisms, including G1 cell cycle arrest, cellular hypertrophy, promotion of protein synthesis, inhibition of protease activity and increased extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of action of RAS is currently unknown, we hypothesize that increased renal renin production caused by severe inflammation has an important role in scar formation because the renin content is reportedly increased depending on the severity of interstitial fibrosis in scarred kidneys. 26,27 As AGT is the only renin substrate in the renal RAS, 18 increased renin produces Ang I from AGT. Ang II converted from increased Ang I induces the expression of transforming growth factor-b1 and causes renal fibrosis through multiple mechanisms, including G1 cell cycle arrest, cellular hypertrophy, promotion of protein synthesis, inhibition of protease activity and increased extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of RAS stimulates the proliferation of renal mesangial cells and interstitial fibroblasts, increases the synthesis and secretion of inflammatory factors by renal inherent cells, and promotes the morphological and functional remodeling of cells [6][7][8][9][10][11] . Because angiotensin II (Ang II) is the major effector in RAS, angiotensin-converting enzyme inhibitors (ACEI) and Ang II type I receptor blockers (ARB) are currently recommended as the first-line medications for the treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that RAS plays a role in pathophysiology of hypertension and organ injury by regulating arterial pressure and sodium homeostasis. Recent studies have shown that aberrant activation of intrarenal RAS contributes to the development and progression of CKD and hypertension (Kagami, 2012;Wen et al, 2010). All components of RAS have been reported to be expressed in various cell types of kidney (Kobori et al, 2007).…”
Section: Introductionmentioning
confidence: 99%